Ensino das ciências: diálogo na educação infantil e a aprendizagem da criança surda, na cidade de Parintins/AM - Amoedo, Francisca Keila de Freitas (2017)
This work entitled: "The teaching of science: dialogue in Early Childhood Education and the learning of the deaf child in the city of Parintins / Am" aims to understand how teaching and learning of deaf children occurs in Early Childhood Education, based on the Teaching of science, considering the mental exercise performed by the child to assimilate the multiple contents taught in the classroom. It seeks to construct a theoretical framework regarding the teaching of the sciences to discuss the teaching and learning process of the deaf child in Early Childhood Education, as well as to describe how deaf children learn the contents worked in a particular Early Childhood Education Center, analyzing how the teaching of Sciences contributes to the learning process of these children in the Early Childhood Education Center. The reflections allowed us to analyze the education of the deaf child in the teaching and learning process, believing that they are able to overcome the barriers that limit their learning and there is a need for quality teaching within a bilingual school for the deaf or school that is prepared to act in Of the inclusive process, respecting the language and identity of the subject, who wants to be deaf or hearing impaired; Society must respect deaf subjects who are still seen and judged as incapable. This analytical reflection was built from the methodological procedures of qualitative research, based on phenomenology; The data collection paths were based on the instruments and techniques of systematic observations in the classroom and on the premises of the school; Semistructured interviews with two female teachers, one from regular education and the other from special education. With the deaf child, writing and drawing activities were developed to enter the learning universe and thus try to see the form and degree of learning of the deaf child. The realization of the deaf students' rights will gain more space when respect for the subject, language and identity of the deaf, with bilingual schools or schools that are prepared for the inclusive process, so that the desired social and school interaction takes place.